EXTENDED CONTINENTAL SHELF REGIME IN INTERNATIONAL LAW: ITS APPLICATION IN INDONESIA - Krisadtyo, Nikki (Indonesian Journal of International Law, 2015)
Indeed, every state intends to explore and exploit its mineral resources. One of the ways to increase the area on which states can explore and exploit its mineral resources is by applying the Extended Continental Shelf (“ECS”) regime. This research explains the development and regulation of the ECS regime which include its requirements, sovereign rights over it, the role of the Commission on the Limits of the Continental Shelf, et cetera. This research then analyzes the ECS regime in Indonesia. This research uses a legal normative research method—which is of an explanatory and descriptiveanalytical character—and uses primary, secondary, and tertiary data. This research shows that Indonesia does not have a strong legal basis to apply the ECS regime nor a utilization plan for its ECS. This regime can be applied in north-west of Sumatera, south of Nusa Tenggara, and north of Papua. Indonesia has made a submission for the ECS in North-West Sumatera which has been accepted. The writer offers some advice: Indonesia should have further legal basis to apply the ECS regime and a utilization plan for its ECS.